2015
DOI: 10.15407/ujpe60.05.0416
|View full text |Cite
|
Sign up to set email alerts
|

Emission Kinetics Of A HgBr Discharge Excilamp

Abstract: A kinetic model of the working medium of a discharge excilamp on the B-X transition of mercury bromide, HgBr, excimer molecules has been proposed. The model explains the nonmonotonic dependence of the excilamp radiation intensity on the partial pressure of mercury dibromide molecules by the attachment of electrons to these molecules. HgBr(X) molecules were found to transit into the HgBr(B) excited state due to their collisions with high-energy electrons, thereby improving the excilamp characteristics. K e y w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…[7], and ω p = 1.32 × 10 16 s −1 , γ ∞ = 3.3095 × 10 13 s −1 , β = 3/5υ F , A = 1. It was reported that the electrostatic approximation could be misleading even in nanoscale optics [29]. Here, we define the relative error of the electrostatic approximation as…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7], and ω p = 1.32 × 10 16 s −1 , γ ∞ = 3.3095 × 10 13 s −1 , β = 3/5υ F , A = 1. It was reported that the electrostatic approximation could be misleading even in nanoscale optics [29]. Here, we define the relative error of the electrostatic approximation as…”
Section: Numerical Resultsmentioning
confidence: 99%
“…First, let us consider the spaser consisting of a nonlocal metallic Au sphere with the radius r c embedded in a semiinfinite host gain medium with permittivity ε G . Without loss of generality, we assume that the metal is described with the Drude permittivity ε T for the transverse electric fields and a spatially dispersive permittivity ε L for the longitudinal electric fields, which are written as [28,29]…”
Section: Model and Theorymentioning
confidence: 99%
“…-state of mercury monoiodide [23]. The collision reaction of mercury diiodide molecules with electrons (5) is a channel for the formation of molecules of mercury monoiodide in the ground state, which rate constant has the value 8•10 -15 m 3 /s [25]. In the collision of electrons with mercury monoidide molecules in…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a kinetic model of the working medium of the HgBr(B-X) lamp [17]. Due to the large difference in the electronic and molecular masses, a steady-state distribution of electrons over energies ε is established much rapidly than the densities of the molecular species changes.…”
Section: Electron-energy Distributionmentioning
confidence: 99%
“…A formula for the rate constant of a molecular transition induced by collisions of the molecule with plasma electrons was derived in our previous work [15,16]. This formula was used in a kinetic study of a HgBr lamp excited by single current pulses [17]. Here, we focus on the calculation of the output characteristics of the HgBr DBD lamp operating in a double-pulse regime.…”
Section: Introductionmentioning
confidence: 99%